Rare Signet Ring Cell Adenocarcinoma of the Colon Metastasis to the Orbit - Colin Bacorn; Lily Koo Lin (Case Reports in Ophthalmological Medicine)
Metastases arising from primary tumors of the gastrointestinal tract are not commonly encountered in the orbit. Colorectal carcinomas are subcategorized based on morphological and genetic characteristics with these distinctions bearing therapeutic and prognostic significance. The behavior of these subcategories, including their propensity for orbital metastasis, differs, and clinicians treating these tumors must be aware of their metastatic profiles. This report describes a 51-year-old female with right upper lid swelling and ptosis ultimately found, what we believe to be, the first reported case of signet ring cell colon carcinoma metastasizing to the levator muscle and superior orbit. This case serves as a reminder to all clinicians to consider orbital metastasis even in malignancies not typically found in this location.